2020
DOI: 10.1007/s15007-020-2550-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity reactions to biologics (part I): allergy as an important differential diagnosis in complex immune-derived adverse events*

Abstract: Purpose: Biotechnological substances (BSs) are strongly relied upon to prevent rejection of transplanted organs, and to treat oncological, allergological, and other inflammatory diseases. Allergic reactions to partly foreign biologics can occur due to their potential immunogenicity. The severity of an immune response to a biological drug may range from no clinical significance to a severe, life-threatening anaphylactic reaction. Methods: Detailed searches were performed on Pubmed, Web of Science, and Google Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 79 publications
0
28
0
6
Order By: Relevance
“…In the European Medicines Agency 2019 assessment report, HSRs of atezolizumab were reported in in up to 10% of patients[ 11 ]. In addition, pruritis and rash were reported in more than 10% of patients[ 6 ]. According to the recent BC Cancer Agency Drug Manual, HSRs including anaphylaxis can be severe in < 1% of the patients, and immune-mediated rash may appear in 8%-18% (severe, 1%) of patients[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the European Medicines Agency 2019 assessment report, HSRs of atezolizumab were reported in in up to 10% of patients[ 11 ]. In addition, pruritis and rash were reported in more than 10% of patients[ 6 ]. According to the recent BC Cancer Agency Drug Manual, HSRs including anaphylaxis can be severe in < 1% of the patients, and immune-mediated rash may appear in 8%-18% (severe, 1%) of patients[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Atezolizumab is a humanized immunoglobulin (Ig)G-1 class antibody that binds to PD-L1 approved by the Food and Drug Administration (FDA) for the treatment of cancer[ 5 ]. The FDA reported severe IRs in 1.3%-1.7% and HSRs in ≤ 1% of cases in which atezolizumab was used[ 6 ]. However, cases of atezolizumab-associated anaphylactic shock are rare.…”
Section: Introductionmentioning
confidence: 99%
“…The drug acts by inhibiting the binding of TNF-alpha to p55 and p75 receptors located on the surface of target cells. Like the other anti-TNF-alpha agents, adalimumab is used for the treatment of inflammatory conditions such as rheumatoid arthritis, ankylosing spondylitis, and psoriatic arthritis [ 5 , 6 ]. In addition, adalimumab is the only drug approved by the FDA for the treatment of moderate-to-severe hidradenitis suppurativa, a chronic, relapsing, inflammatory disorder characterized by the presence of painful nodules, abscesses, sinus tracks, and scarring mainly in the inguinal and axillary regions [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a comprehensive review of databases and scientific literature has shown that, on the one hand, the nomenclature of hypersensitivity reactions to biologicals is not harmonized, so that data on the prevalence and incidence of “real” allergic and anaphylactic reactions to the various biologicals cannot be reliably collected [ 88 , 89 ]. Furthermore, the symptomatology of anaphylaxis may vary between different biologicals [ 87 ].…”
Section: Hypersensitivity Reactions To Biologicalsmentioning
confidence: 99%